2021
DOI: 10.3390/biom11121755
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA—Is the Circle Perfect?

Abstract: Circular RNA (circRNA) is a distinct class of non-coding RNA produced, in principle, using a back-splicing mechanism, conserved during evolution, with increased stability and a tissue-dependent expression. Circular RNA represents a functional molecule with roles in the regulation of transcription and splicing, microRNA sponge, and the modulation of protein–protein interaction. CircRNAs are involved in essential processes of life such as apoptosis, cell cycle, and proliferation. Due to the regulatory role (upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 95 publications
(115 reference statements)
0
28
0
2
Order By: Relevance
“…Circular RNA (circRNA) comprises a different class of noncoding RNA produced; it is a functional molecule with important roles in regulating transcription and splicing, microRNA sponging, and modulating protein–protein interactions. CircRNA can be classified into exonic RNAs (ecircRNAs) , formed by exons, circular intronic RNAs (ciRNAs) , formed by introns, and exon-intron circRNAs (EIciRNAs) , formed by both exons and introns [ 124 ]. More studies have indicated that circRNAs may be associated with the risk of nerve diseases, atherosclerotic vascular diseases, cancer, and autoimmune diseases, suggesting it is a novel diagnostic and prognostic biomarker candidate, as well as a new therapeutic target for different disorders [ 125 , 126 , 127 , 128 ].…”
Section: Human Leukocyte Antigen B27 (Hla-b27) and Newer Genetic Biom...mentioning
confidence: 99%
“…Circular RNA (circRNA) comprises a different class of noncoding RNA produced; it is a functional molecule with important roles in regulating transcription and splicing, microRNA sponging, and modulating protein–protein interactions. CircRNA can be classified into exonic RNAs (ecircRNAs) , formed by exons, circular intronic RNAs (ciRNAs) , formed by introns, and exon-intron circRNAs (EIciRNAs) , formed by both exons and introns [ 124 ]. More studies have indicated that circRNAs may be associated with the risk of nerve diseases, atherosclerotic vascular diseases, cancer, and autoimmune diseases, suggesting it is a novel diagnostic and prognostic biomarker candidate, as well as a new therapeutic target for different disorders [ 125 , 126 , 127 , 128 ].…”
Section: Human Leukocyte Antigen B27 (Hla-b27) and Newer Genetic Biom...mentioning
confidence: 99%
“…The development of high-throughput sequencing technology has led to the identification of an increasing number of circRNAs ( Kai Wang et al, 2022 ). Most circRNAs originate from exons in the coding regions of genes, whereas others originate from the 3′-UTR, 5′-UTR, introns, intergenic regions and antisense RNAs ( Caba et al, 2021 ). CircRNAs are classified into four types, namely, exonic circRNAs (ecircRNAs), circular intronic RNAs (ciRNAs), exonic-intronic circRNAs (eiciRNAs), and tRNA intronic circRNAs (tricRNAs) ( Wenqing Zhang et al, 2021 ).…”
Section: Noncoding Rnas In Cancermentioning
confidence: 99%
“…NcRNAs include, among others, also circular RNAs (circRNAs) [ 15 , 16 ] and long non-coding RNAs (lncRNAs) [ 17 ] that can be aberrantly expressed in various diseases. CircRNA are molecules produced as covalently closed continuous loops that lack 3′- and 5′-ends and, therefore, have a higher tolerance to degradation by RNase R exonuclease [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA are molecules produced as covalently closed continuous loops that lack 3′- and 5′-ends and, therefore, have a higher tolerance to degradation by RNase R exonuclease [ 15 ]. They can be classified based on their origin as exonic circRNA (ecircRNA), if they are produced by exon splicing, circular intronic RNA (ciRNA), if the molecule derives from an intronic region splicing, exon-intron circRNA (EIciRNA), if the splicing process regards both exons and introns [ 16 ].…”
Section: Introductionmentioning
confidence: 99%